Improving root cause analysis through the integration of PLM systems with cross supply chain maintenance data - Madenas, N; Tiwari, Ashutosh; Turner, Christopher J.; Peachey, Sophie; Broome, S (Springer, 2016)
The purpose of this paper is to demonstrate a system architecture for integrating Product Lifecycle Management (PLM) systems with cross supply chain maintenance information to support root-cause analysis. By integrating product-data from PLM systems with warranty claims, vehicle diagnostics and technical publications, engineers were able to improve the root-cause analysis and close the information gaps. Data collection was achieved via in-depth semi-structured interviews and workshops with experts from the automotive sector. Unified Modelling Language (UML) diagrams were used to design the system architecture proposed. A user scenario is also presented to demonstrate the functionality of the system.
Keywords: Root cause analysis; Warranty; Supplier Integration; Product Lifecycle Management; Information systems